2023
DOI: 10.1007/s40519-023-01547-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related changes in eating disorder pathology, emotional and binge eating and need for care: a systematic review with frequentist and Bayesian meta-analyses

Abstract: Purpose The COVID-19 pandemic has been a leading cause of stress and feelings of loss of control, both of which have been related to eating disorder (ED) pathology onset and deterioration. We aim to estimate the magnitude of changes in the prevalence rates of, and indicators for, ED psychopathology in the face of the COVID-19 pandemic. Method Pre-registered systematic review with frequentist and Bayesian meta-analyses. Searches for eligible studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…Still, we found a significant increase in the admission rate of trifold-affected youth showing ED, DD, and AD, indicating a small group of patients with ED with strongly increased severe mental health problems during COVID-19. Other studies reported a generally increased DD comorbidity in ED inpatients ( 25 , 28 ) but, similar to our results, no changes in AD comorbidity rates ( 28 , 43 , 45 ).…”
Section: Discussionsupporting
confidence: 90%
“…Still, we found a significant increase in the admission rate of trifold-affected youth showing ED, DD, and AD, indicating a small group of patients with ED with strongly increased severe mental health problems during COVID-19. Other studies reported a generally increased DD comorbidity in ED inpatients ( 25 , 28 ) but, similar to our results, no changes in AD comorbidity rates ( 28 , 43 , 45 ).…”
Section: Discussionsupporting
confidence: 90%
“…The COVID-19 pandemic has exerted a negative effect on the prevalence rates of eating disorders (EDs), their symptoms, psychiatric comorbidity, and the need for care, but the range and the magnitude of this effect is still unknown. Indeed, many results suggest that the COVID-19 pandemic was associated with a widespread negative effect on EDs in patients and in the general population [3]. A systematic review synthesizes the impact of the COVID-19 pandemic on BED new onset and course, in particular after the introduction of restrictive measures to reduce the infection (lockdown), confirming its negative impact [4].…”
Section: Introductionmentioning
confidence: 94%
“…Any potential doubts about the impact of COVID-19 on mental health have been largely put to rest by the most recent papers on the topic [ 90 , 91 , 92 , 93 , 94 ]. Loneliness, physical exhaustion, sleep disturbances, and anhedonia linked to compulsive or addictive behaviors such as binge-eating [ 95 , 96 ], substance abuse [ 97 ], and digital reward craving [ 98 ] were identified asbeing linked to suicidal ideation [ 95 , 99 , 100 ]—in particular, in younger individuals—during and after the pandemic. These reflect some of the most negative effects of pandemic-related adversity on mental health worldwide.…”
Section: Covid-19 Pandemic and Mental Healthmentioning
confidence: 99%